2017
DOI: 10.1007/s12032-017-0915-4
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor 1 gene polymorphism in women with breast cancer

Abstract: Breast cancer is a disease of unknown etiology; however, the major risk factors are genetic alterations. Studies have demonstrated an association between insulin-like growth factor 1 (IGF-1) gene polymorphism and cell proliferation and reduced apoptosis, in addition to its role in breast cancer growth and aggressiveness. Two polymorphic variants of the IGF-1 gene are highlighted in association with breast cancer, rs6220 and rs7136446, although controversy exists as to this relationship. The current study inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…In a study recruiting 110 colorectal cancer cases and 137 breast cancer cases, the genetic polymorphisms of IGF-1 were evaluated. The authors reported that IGF-1 SNPs were correlated with cancer risk and prognosis [ 20 ]. In addition, another recent study provided some evidence that targeting IGF-1R might suppress osteosarcoma progression, highlighting the role that the IGF-1 family plays in osteosarcoma [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study recruiting 110 colorectal cancer cases and 137 breast cancer cases, the genetic polymorphisms of IGF-1 were evaluated. The authors reported that IGF-1 SNPs were correlated with cancer risk and prognosis [ 20 ]. In addition, another recent study provided some evidence that targeting IGF-1R might suppress osteosarcoma progression, highlighting the role that the IGF-1 family plays in osteosarcoma [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] Therefore, breast cancer is a multifactorial disease, and one of the main risk factors is genetic alterations. [ 7 9 ] In this regard, one of the genes to draw attention due to its possible association with breast cancer tumorigenesis is the insulin-like growth factor 1 (IGF-1) gene. IGF-1 is located on the long arm of chromosome 12 and covers an area of over 80 kb of genomic DNA.…”
Section: Introductionmentioning
confidence: 99%
“…For the year 2018, approximately 2.1 million new cases of breast cancer were estimated to occur worldwide [3]. Breast cancer is a complex disease of unknown and multifactorial etiology, in which one of the main risk factors is genetic alteration [4,5]. Thus, genetic mutations of breast cancer (BRCA) 1 and 2 genes are related to the increased risk of hereditary breast and ovarian cancer over time [6], however, the participation of genes in breast cancer has not yet been fully elucidated [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer is a complex disease of unknown and multifactorial etiology, in which one of the main risk factors is genetic alteration [4,5]. Thus, genetic mutations of breast cancer (BRCA) 1 and 2 genes are related to the increased risk of hereditary breast and ovarian cancer over time [6], however, the participation of genes in breast cancer has not yet been fully elucidated [4,5]. Thus, changes in expression levels of the insulin-like growth factor 1 [IGF-1] gene have been evaluated in breast cancer, however, there is a need for further elucidation of the association between changes in IGF-1 levels and increase in the risk, survival, and disease progression of breast cancer [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation